BonnMu: A Sequence-Indexed Resource of Transposon-Induced Maize Mutations for Functional Genomics Studies . Issue 2 (7th August 2020) - Marcon, Caroline; Altrogge, Lena; Win, Yan Naing; Stöcker, Tyll; Gardiner, Jack M.; Portwood, John L.; Opitz, Nina; Kortz, Annika; Baldauf, Jutta A.; Hunter, Charles T.; McCarty, Donald R.; Koch, Karen E.; et al.
Abstract : A European sequence-indexed library of Mutator insertions provides an important resource for functional genetics studies of maize. Abstract: Sequence-indexed insertional libraries in maize ( Zea mays ) are fundamental resources for functional genetics studies. Here, we constructed a Mutator ( Mu ) insertional library in the B73 inbred background designated BonnMu . A total of 1, 152 Mu -tagged F2 -families were sequenced using the Mu -seq approach. We detected 225, 936 genomic Mu insertion sites and 41, 086 high quality germinal Mu insertions covering 16, 392 of the annotated maize genes (37% of the B73v4 genome). On average, each F2 -family of the BonnMu libraries captured 37 germinal Mu insertions in genes of the Filtered Gene Set (FGS). All BonnMu insertions and phenotypic seedling photographs of Mu- tagged F2 -families can be accessed via MaizeGDB.org . Downstream examination of 137, 410 somatic and germinal insertion sites revealed that 50% of the tagged genes have a single hotspot, targeted by Mu . By comparing our BonnMu (B73) data to the UniformMu (W22) library, we identified conserved insertion hotspots between different genetic backgrounds. Finally, the vast majority of BonnMu and UniformMu transposons was inserted near the transcription start site of genes. Remarkably, 75% of all BonnMu insertions were in closer proximity to the transcription start site (distance: 542 bp) than to the start codon (distance: 704 bp), which corresponds to open chromatin, especially in the 5′ region of genes. Our European sequence-indexed library of Mu insertions provides an important resource for functional genetics studies of maize.